The Role of the p21-Activated Kinase Family in Tumor Immunity - Lu, Tianqi; Huo, Zijun; Zhang, Yiran; Li, Xiaodong (International journal of molecular sciences, 2025)
The p21-activated kinases (PAKs) are a group of evolutionarily conserved serine/threonine protein kinases and serve as a downstream target of the small GTPases Rac and Cdc42, both of which belong to the Rho family. PAKs play pivotal roles in various physiological processes, including cytoskeletal rearrangement and cellular signal transduction. Group II PAKs (PAK4-6) are particularly closely linked to human tumors, such as breast and pancreatic cancers, while Group I PAKs (PAK1-3) are indispensable for normal physiological functions such as cardiovascular development and neurogenesis. In recent years, the association of PAKs with diseases like cancer and the rise of small-molecule inhibitors targeting PAKs have attracted significant attention. This article focuses on the analysis of PAKs’ role in tumor progression and immune infiltration, as well as the current small-molecule inhibitors of PAKs and their mechanisms.